Assessment of External Alarm System Performance and Quality Using ISO/IEC 25010 Framework - M Aidil Irawan (PT. Lentera Ilmu Publisher, 2026)
This study assesses the performance and quality of an external alarm system using the ISO/IEC 25010 framework. The evaluation covers eight quality characteristics: functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability, and portability. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The measurement model results indicate that all constructs meet the required validity and reliability criteria. Outer loadings range from 0.730 to 0.956, exceeding the recommended threshold of 0.70. The Average Variance Extracted (AVE) values are above 0.50, confirming convergent validity. Furthermore, Cronbach’s Alpha and Composite Reliability values exceed 0.70 for all constructs, demonstrating strong internal consistency. These findings confirm that the external alarm system meets established software quality standards and performs reliably across multiple dimensions. The validated model provides a robust foundation for further structural analysis and quality improvement strategies.